Respon Vaksinasi ND Ayam IPB D1 yang Dipelihara pada Lingkungan Lahan Kering - Mandala, Graziela Angelicha; Tangkonda, Elisabet; Sanam, Maxs U. E. (JURNAL KAJIAN VETERINER, 2023)
Newcastle Disease (ND) is one of the diseases that causes large losses in the poultry farming industry. Vaccination can reduce symptoms and protect chickens from ND. High maintenance temperatures on dry land can interfere with immune cell production. IPB D1 chicken is a chicken resulting from a cross between local chickens and purebred chickens that is resistant to disease. The aim of the research was to determine the response of IPB D1 chicken vaccination against Newcastle Disease (ND) and compare the antibody titers of IPB D1 chickens in tropical regions that were vaccinated with ND via the drinking water and intramuscular routes. This research was carried out on 30 IPB D1 chickens divided into three groups, namely , group A vaccination via drinking water, group B vaccination via intramuscular and control group (C) with the aim of comparing the antibody titers of IPB D1 chickens vaccinated via drinking water and intramuscularly and to determine the response of vaccination of IPB D1 chickens against Newcastle Disease. Pre- and post-vaccination immune responses were tested using hemagglutination inhibition (HI). The results showed that the group of chickens vaccinated through drinking water had an average pre-vaccination antibody titer of 1.8 ± 0.91 log 2, at week 2 post-vaccination it was 3.3 ± 2.05 log 2, at week 4 post-vaccination it was 5 .3 ± 2.31 log 2 and at the 8th week post-vaccination 3.2 ± 1.22 log 2. The average antibody titer in the group of chickens vaccinated via intramuscular pre-vaccination was 1.6 ± 0.51 log 2, at week 2. -2 post-vaccination 5.4 ± 3.09 log 2, at the 4th week post-vaccination 4.89 ± 2.71 log 2 and at the 8th week post-vaccination 3.56 ± 2.01. It was concluded that ND vaccination via the drinking water and intramuscular route was able to increase antibodies to reach an average titer above 4 HI log 2 within a period of at least four weeks after administering the vaccine to IPB D1 chickens kept in a dry land environment. The antibody titer of IPB D1 chickens vaccinated intramuscularly increased faster than those vaccinated through drinking water.